2021
DOI: 10.1177/01461672211059700
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal Consequences of Deceptive Expressions of Sadness

Abstract: Emotional expressions evoke predictable responses from observers; displays of sadness are commonly met with sympathy and help from others. Accordingly, people may be motivated to feign emotions to elicit a desired response. In the absence of suspicion, we predicted that emotional and behavioral responses to genuine (vs. deceptive) expressers would be guided by empirically valid cues of sadness authenticity. Consistent with this hypothesis, untrained observers (total N = 1,300) reported less sympathy and offere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…Feeling sad arises with a valued loss. Exploring feeling sad in different disciplines indicated that feeling sad arises from a valued loss (Bunkers, 2010;Draper, 1999;Freed & Mann, 2007;Garg, 2019;Garg & Lerner, 2013;Gunderson et al, 2021;Knowles & Langley, 2012;Lazarus, 1991;Levenson, 1999;Mouchet-Mages & Baylé, 2008;Nesse, 1990;Phillips, 2009;Rivers et al, 2006;Smith & Lazarus, 1993;Tahlier et al, 2013;Zaid et al, 2021). For instance, Garg (2019) emphasized the importance of feeling sad as the most experienced emotion among all negative emotions.…”
Section: Exploring With Pattern Preferencesmentioning
confidence: 99%
“…Feeling sad arises with a valued loss. Exploring feeling sad in different disciplines indicated that feeling sad arises from a valued loss (Bunkers, 2010;Draper, 1999;Freed & Mann, 2007;Garg, 2019;Garg & Lerner, 2013;Gunderson et al, 2021;Knowles & Langley, 2012;Lazarus, 1991;Levenson, 1999;Mouchet-Mages & Baylé, 2008;Nesse, 1990;Phillips, 2009;Rivers et al, 2006;Smith & Lazarus, 1993;Tahlier et al, 2013;Zaid et al, 2021). For instance, Garg (2019) emphasized the importance of feeling sad as the most experienced emotion among all negative emotions.…”
Section: Exploring With Pattern Preferencesmentioning
confidence: 99%
“…The tipping point framework suggests that response biases, which consistently tip in the direction of thinking and saying others are telling the truth (Levine, 2014; Levine et al, 1999), are influenced by social norms and costs associated with norm violations (ten Brinke et al, 2016). Claims to have seen someone tell a lie are tantamount to branding that person a liar (Uhlmann, Pizarro, & Diermeier, 2015), and such accusations violate social trust norms which come at a cost for the accuser (Gunderson, Pence, & ten Brinke, 2018). Impugning the moral character of another person has been shown to reflect negatively on the accuser’s own moral standing (Critcher, Inbar, & Pizarro, 2013), and signaling distrust can erode valuable social relationships (Kramer, 1999).…”
Section: The Tipping Point Framework Of Human Lie-detectionmentioning
confidence: 99%